ANNULMENT OF NATIONAL SHARIA ARBITRATION BODY (BASYARNAS) DECISIONS BY RELIGIOUS COURTS IN SHARIA ECONOMIC DISPUTES - Annisa; Mujib, Abdul (Universitas Muhammadiyah Surabaya, 2024)
BASYARNAS decision should be final and binding, but it can still be canceled by the Religious Court if it is considered unfair or detrimental to one of the parties. However, in reality, decisions in the Religious Court are also often found to be weak, such as the lack of inclusion of legal basis or consideration of relevant aspects related to the decision. This research method is qualitative with the type of case study that uses a normative legal approach to examine the legal considerations used by the judge in deciding the case. The results showed that the cancellation of the BASYARNAS decision was granted because it was proven that there was deception by the Respondents against the Peace Deed, the determination of interest and fines which were considered unfounded. However, the legal basis used by the judge is still incomplete. Moreover, in terms of the lack of good faith in dispute resolution. The legal consequences of this annulment are the elimination of the provisions of the BASYARNAS-MUI JT Peace Decision Number xx/BASYARNAS-xxx/xxxx so that SHM number xxx cannot be executed because lawsuit Number xxxx/Pdt.G/xxxx/PA.xxx is declared lacking parties so it cannot be accepted, and Respondent II must renew the contract based on the clauses in the decision. Keywords: BASYARNAS, Decision Cancellation, Legal Effects.